Exploring the bilingual advantage: manipulations of similarity and second language immersion in a Stroop task. Issue 1 (2nd January 2019) - Hannaway, Naomi; Opitz, Bertram; Sauseng, Paul
ABSTRACT: To explain varying previous results as to whether bilinguals show an advantage over monolinguals in inhibitory control, two hypotheses have been suggested. The Bilingual Inhibitory Control Advantage (BICA) hypothesis proposes a bilingual advantage specific to the presence of conflict. In contrast, the Bilingual Executive Processing Advantage (BEPA) hypothesis proposes a global advantage in processing, across all contexts. The present research contrasts these hypotheses by investigating the effects of second language immersion and similarity of colour terms across languages on the bilingual Stroop task. Ten English and ten German native speakers, residing in Munich, Germany, completed a bilingual Stroop task using stimuli with colour terms which were similar or dissimilar between the two languages. Event-related potentials were recorded alongside behavioural data. Dissimilar stimuli showed greater costs, reflected by increased reaction times (RTs), more negative N400 amplitudes and more positive Late Positive Component (LPC) amplitudes, than similar stimuli. Participants who were immersed in a second language environment experienced greater costs, which were specific to conflict trials for RT and LPC measures, but occurred across all trial types during the N400 window. It was concluded that in contrast to previous research only supporting BEPA, there is also evidence for the BICA hypothesis.